2018
DOI: 10.3389/fpls.2018.01401
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Growth, Yield, and the Nutraceutical and Antioxidative Potential of Soybean Through the Use of Synthetic Biostimulants

Abstract: Improvement of crop cultivation technologies is focused on increasing crop productivity and improving yield quality, and at the same time on minimizing risks posed to the natural environment. The use of biostimulants contributes to the increase in the productivity of plants, especially under their exposure to stress induced by negative environmental stimuli. A field experiment was conducted in three growing seasons (2014–2016). Seeds of soybean of the Atlanta cultivar were sown in the third decade of April. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 89 publications
3
44
0
2
Order By: Relevance
“…However, this increasing trend was not consistent throughout the years, and the authors suggested a combined effect of growing conditions and biostimulants application, whereas the beneficial effect of seaweed filtrates on total phenols content was attributed to osmotic stress induced by the high content of A. nodosum filtrates in mannitol . Similar results have been reported for total phenols and flavonoids contents of soybean seeds after the application of two synthetic biostimulants (Atonik and Tytanit), where, despite the different response being observed during a 3 year study, the application of biostimulants in a high single doses gave consistently the best results . Polyphenols and flavonoids content of seeds from three soybean cultivars was also affected by natural biostimulants application such as Fylloton (a complex of amino acids and seaweed extracts) in a dose and cultivar‐dependent manner .…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…However, this increasing trend was not consistent throughout the years, and the authors suggested a combined effect of growing conditions and biostimulants application, whereas the beneficial effect of seaweed filtrates on total phenols content was attributed to osmotic stress induced by the high content of A. nodosum filtrates in mannitol . Similar results have been reported for total phenols and flavonoids contents of soybean seeds after the application of two synthetic biostimulants (Atonik and Tytanit), where, despite the different response being observed during a 3 year study, the application of biostimulants in a high single doses gave consistently the best results . Polyphenols and flavonoids content of seeds from three soybean cultivars was also affected by natural biostimulants application such as Fylloton (a complex of amino acids and seaweed extracts) in a dose and cultivar‐dependent manner .…”
Section: Resultssupporting
confidence: 78%
“…34 Similar results have been reported for total phenols and flavonoids contents of soybean seeds after the application of two synthetic biostimulants (Atonik and Tytanit), where, despite the different response being observed during a 3 year study, the application of biostimulants in a high single doses gave consistently the best results. 9 Polyphenols and flavonoids content of seeds from three soybean cultivars was also affected by natural biostimulants application such as Fylloton (a complex of amino acids and seaweed extracts) in a dose and cultivar-dependent manner. 35 The beneficial effect of biostimulants on phenolic compounds composition and content of snap bean pods was also reported in the case of garlic clove extracts and associated with its high content in phytohormones such as jasmonic and salicylic acids.…”
Section: Comparative Analysis Of Phenolic Content In Each Seed and Pomentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its broad use, it is called a "wonderful crop" [4]. However, this plant is sensitive to unfavourable climatic conditions [5]. Thus, to ensure its effective protection against biotic and abiotic factors, it is recommended to use it in the cultivation of biostimulants, which may improve the biochemical, morphological, and physiological processes that take place in a plant [6][7][8].…”
Section: Introductionmentioning
confidence: 99%